Monitoring Recently Acquired HIV Infections in Amsterdam, The Netherlands: The Attribution of Test Locations - Slurink, Isabel A. L.; van de Baan, Frank; van Sighem, Ard I.; van Dam, Alje P.; van de Laar, Thijs J. W.; de Bree, Godelieve J.; van Benthem, Birgit H. B.; Op de Coul, Eline L. M. (Frontiers in Reproductive Health, 2021)
Background: Surveillance of recent HIV infections (RHI) using an avidity assay has been implemented at Dutch sexual health centres (SHC) since 2014, but data on RHI diagnosed at other test locations is lacking. Setting: Implementation of the avidity assay in HIV treatment clinics for the purpose of studying RHI among HIV patients tested at different test locations. Methods: We retrospectively tested leftover specimens from newly diagnosed HIV patients in care in 2013-2015 in Amsterdam. Avidity Index (AI) values≤0.80 indicated recent infection (acquired≤6 months prior to diagnosis), and AI>0.80 indicated established infection (acquired>6 months prior to diagnosis). An algorithm for RHI was applied to correct for false recency. Recency based on this algorithm was compared with recency based on epidemiological data only. Multivariable logistic regression analysis was used to identify factors associated with RHI among men who have sex with men (MSM). Results: We tested 447 specimens with avidity; 72% from MSM. Proportions of RHI were 20% among MSM and 10% among heterosexuals. SHC showed highest proportions of RHI (27%), followed by GPs (15%), hospitals (5%) and other/unknown locations (11%)(p<.001). Test location was the only factor associated with RHI among MSM. A higher proportion of RHI was found based on epidemiological data compared to avidity testing combined with the RHI algorithm. Conclusion: SHC identify more RHI infections compared to other test locations, as they serve high-risk populations and offer frequent HIV testing. Using avidity-testing for surveillance purposes may help targeting prevention programs, but the assay lacks robustness and its added value may decline with improved, repeat HIV testing and data collection.